2022
DOI: 10.1002/smll.202202161
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Nanozymatic Nanoparticles Induce Ferroptosis and Apoptosis through Tumor Microenvironment Manipulation for Cancer Therapy

Abstract: It is highly desirable to design a single modality that can simultaneously trigger apoptosis and ferroptosis to efficiently eliminate tumor progression. Herein, a nanosystem based on the intrinsic properties of tumor microenvironment (TME) is designed to achieve tumor control through the simultaneous induction of ferroptosis and apoptosis. CuCP molecules are encapsulated in a liposome‐based nanosystem to assemble into biocompatible and stable CuCP nanoparticles (CuCP Lipo NPs). This nanosystem intrinsically po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…In addition, due to the excellent photothermal effect of Bi 2 Te 3 nanosheets, the local heat generated by NIR-II light irradiation at 1064 nm not only directly ablates tumor cells but also enhances Au–Pd-catalytic-mediated tumor therapy. Yuan et al designed a nanosystem based on the intrinsic properties of TME to achieve tumor control by simultaneously inducing iron sagging and apoptosis. The nanosystem with intrinsic nanozyme activity and photothermal properties synergistically increased the intracellular lipid-active oxide species, induced the onset of iron sagging and apoptosis, and completely eradicated the tumor in vivo (Figure ).…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, due to the excellent photothermal effect of Bi 2 Te 3 nanosheets, the local heat generated by NIR-II light irradiation at 1064 nm not only directly ablates tumor cells but also enhances Au–Pd-catalytic-mediated tumor therapy. Yuan et al designed a nanosystem based on the intrinsic properties of TME to achieve tumor control by simultaneously inducing iron sagging and apoptosis. The nanosystem with intrinsic nanozyme activity and photothermal properties synergistically increased the intracellular lipid-active oxide species, induced the onset of iron sagging and apoptosis, and completely eradicated the tumor in vivo (Figure ).…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 99%
“…Photothermal therapy induces tumor iron death and apoptosis. Reprinted with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 99%
“…This study showed that CuCP Lipo NP nanozymes synergistically induced ferroptosis and apoptosis in vivo to suppress tumor growth, showing great potential for clinical application in cancer therapy. 65…”
Section: Application Of Nanozymes To Cancer Therapymentioning
confidence: 99%
“…This study showed that CuCP Lipo NP nanozymes synergistically induced ferroptosis and apoptosis in vivo to suppress tumor growth, showing great potential for clinical application in cancer therapy. 65 In addition, Chang et al reported a novel strategy based on a single Pd atom nanozyme (Pd SAzyme) that enhanced the effectiveness of mild-temperature photothermal therapy (PTT) in cancer treatment by inducing ferroptosis. They constructed a nitrogen-coordinated carbon-supported Pd SAzyme by stripping a single atom from metal NPs.…”
Section: Nanozyme Applications Based On Ferroptosis Regulationmentioning
confidence: 99%
“…Thus, enhancing supplement of oxygen into tumor mass is a reasonable strategy to improve the therapeutic efficacy of SDT. Currently, various strategies have been designed to alleviate tumor hypoxia, such as introduction of microbubbles containing oxygen, in situ O 2 generation by metals, or catalase reacting with intratumoral H 2 O 2 and hemoglobin (Hb). …”
Section: Introductionmentioning
confidence: 99%